Penelusuran Hukum Penting Bagi Pengemban Profesi Hukum (Suatu Studi Tentang Profesi Advokat Sebagai Pengemban Profesi Hukum) (Lex Jurnalica, 2008)
Challenge that faced lawyer as profession caretaker law in decade latest this we can say is not light. Therefore, so that can follow very latest development in the world of science law best step do way of law. From way of law, matters about science development law, judge decision and very latest law and regulation knowable by profession caretaker of law. Specialer again for lawyer profession caretaker, various case that faced more complexer. In atmosphere likes this, possible norms that regulate about case that being faced not yet being regulated peculiarly in law and regulation aloof. At here feeled important to do way of law may be is not found exactly in some case,Â  but resemble with case there. For that can be made reference in finish also law opinion that asked to lawyer as law profession caretaker.Keywords: The Way ofÂ  law, law profession caretaker; lawyer